The Formulation of PPAT Legal Accountability in Issuance of Purchase Deeds - Robiatun Nasekah, Dwi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
The purpose of this study is to find out what factors cause the sale and purchase deed to be null and void and how the PPAT's responsibility for the sale and purchase deed is null and void. This study uses a normative juridical approach. Primary and secondary data collection was obtained by interview and literature study, then analyzed using qualitative analysis methods. Analysis on the study of decision No.32/Pdt-G/2011/PN-BNA, the sale and purchase agreement was canceled because the plaintiff's deceased wife sold the land object without the consent of the plaintiff as her husband. Referring to the sound of Article 1320 of the Civil Code regarding the legal requirements of an agreement. Where in this case there is no agreement between the land owner, namely the husband and wife as the holders of legal land rights to the buyer. Regarding the cancellation of the Sale and Purchase Deed in the said decision, the PPAT is subject to administrative responsibility as explained in Article 62 PP Number 24 of 1997, without reducing the possibility of being sued for compensation by parties who suffer losses resulting from neglect of these provisions. The future PPAT accountability formulation refers to Wet Van 25 Ventose Jaar Xi Op Het Notarisambt above. As reads in Art 96 and 97 Wet Van 25 Ventose Jaar Xi Op Het Notarisambt explains that the responsibility of a notary/PPAT can be held criminally and administratively accountable together. For PPATs, PPATs should be even more active in studying the notarial law and all related regulations, because regulatory laws are always changing and may increase. In addition, it is hoped that people who will carry out a land sale and purchase transaction can comply with the principle of truth and cash in executing the deed of sale and purchase. If the land to be purchased is joint property, then the husband and wife must agree, not just one.Keyword: Dispute; Land; Transfer.